Power-load curve in trained sprinters - Alcaraz, P. E.; Romero-Arenas, S.; Vila, H.; Ferragut, C. (The Journal of Strength and Conditioning Research, 2011)
The levels of lower-limb strength and power can distinguish between athletes of different levels in a number of sports, specifically in sprinting. In this sense, the purposes of this study were (a) to define the power-load curve in a modified half squat machine in trained sprinters in the competitive cycle and (b) to correlate the peak power (PP) production with 60-m sprint performance. In this sense, a cross-sectional study was carried out with 10 national level sprinters. After the calculation of 1 repetition maximum (1RM) of the participants, a progressive test, which consisted of moving loads of 30, 45, 60, 70, and 80% of the 1RM as quickly as possible in the concentric phase, was performed. It was found that PP occurred at 60% of 1RM. The power output with all loads was not significantly different (p <= 0.05) from each other. No significant correlations were found between 60-m performance and PP with the different loads. Therefore, we may conclude that the sprinters of national level analyzed present values of PP output, in the competitive period, near to 60% of 1RM in the half squat exercise; however, this power is not significantly different from the other loads.